PRODUCTION OF INVERTASE FROM ASPERGILLUS NIGER USING FRUIT PEEL WASTE AS A SUBSTRATE - K. MEHTA,; J.S. DUHAN, (International Journal of Pharma and Bio Sciences, 2014)
Aim of present study was production, purification and characterization of invertase by Aspergillus niger (isolated from soil) using fruit peel waste as a substrate. Screening of various fungi grown on potato dextrose-agar (PDA) was done using liquid medium of 50% sucrose-Cazpek. After incubation at 28ËšC for 10 days, the invertase activity was determined in the culture filtrate using Fehling’s solution. The positive result was indicated by brown and green precipitate. Sugar generated by the hydrolysis of sucrose was measured by DNSA method. A. niger produced maximum invertase on 4th day of incubation under optimized culture conditions i.e. pH 5.0, temperature 30°C, inoculum size 106 -108 spores/ml in Czapek Dox using fruit peel waste as a substrate by submerged fermentation (SmF). Invertase enzyme was also produced by A. niger from other carbon source (lactose, fructose, sucrose etc.) as substrate. Out of these fructose showed maximum production of invertase. Fruit peel may be proved a good economic source for invertase production on an industrial scale.